Effects of two debittering processes on the alkaloid content and quality characteristics of lupin (Lupinus mutabilis Sweet). (24th January 2020) - Villacrés, Elena; Álvarez, Javier; Rosell, Cristina
Abstract: BACKGROUND: The presence of quinolizidine alkaloids (QAs) in the species Lupinus mutabilis Sweet limits the expansion of its consumption and use, despite its high protein content. The objective of this research was therefore to determine the effect of two thermal treatments, aqueous (ATT) and saline (STT), on the QAs and total protein content, as well as on the texture (fracturability and hardness), visual perception attributes – hue ( H* ), luminosity ( L* ) and chromatism ( C* ) – and grain size in three lupin varieties (INIAP‐450, INIAP‐451, and Criollo). The water consumption required by each treatment was also measured. RESULTS: The debittering process with ATT helped to concentrate the total nitrogen by 560 g kg −1 and decreased the grain hardness to 2037 gf (grams of force) in the Criollo variety, while the chromatic parameters H* and C* increased in the three varieties. The STT treatment was more efficient than the ATT treatment in terms of the time required and the volume of water used to reduce the QAs to safe levels for consumption (2.5–3.5 g kg −1 ). The size of the grain increased to four times its original size; the luminosity L* decreased during cooking to a value of 41.49 in the Criollo variety and then increased to 57.42 during grain washing. CONCLUSIONS: The STT treatment is advisable for lupin debittering, although the extent of the effect was dependent on the variety. © 2020 Society of Chemical Industry